Poultry quality evaluation : quality attributes and consumer values - Petracci, Massimiliano; Berri, Cecile (Woodhead Publishing in food science, technology, and nutrition., 2017)
Poultry Quality Evaluation: Quality Attributes and Consumer Values provides a new reference source that covers these aspects with the same scientific authority as texts on traditional poultry meat quality values. The book's first section explores new developments in our understanding of how muscle structure affects the eating qualities of cooked meat. The second section highlights new techniques for measuring, predicting, and producing poultry meat quality and how these new techniques help us minimize variability in eating quality and/or maximize value. The final section identifies the current qualities of consumer and public perceptions, including what is sustainable, ethical, desirable, and healthy in poultry production and consumption. Brings together top researchers in the field to provide a comprehensive overview of the new elements of poultry quality evaluation. Provides a comprehensive reference source on poultry with the same scientific authority as texts on more broad traditional meat quality values. Contains contributions from editors who are very well known and highly respected in the field.